Management of Educational Technology in the World of Education: Manajemen Teknologi Pendidikan Dalam Dunia Pendidikan - Sukatin; Anisa Ramadani; Dinda Dwi Ariani; Ihsan Nuralim (Institute of Educational, Research, and Community Service, 2024)
In the current era, technology is frequently utilized for facilitating learning, both by educators and students. However, the advancements in modern technology not only bring positive impacts to the realm of education but may also lead to negative consequences, affecting changes in student behavior and posing a threat to educational norms and regulations. The objective of this research is to delve into the management of educational technology. The chosen research method is literature review, specifically gathering information from journals, books, and other sources. The findings underscore the significance of maintaining professionalism as users when harnessing technology effectively, ensuring the smooth progression of technological developments. Technology holds the potential to streamline tasks; therefore, let's optimize its utilization.